High seropositivity of IgG and IgM antibodies against cytomegalovirus (CMV) among HIV-1 seropositive patients in Ilorin, Nigeria (2015)
Background: Human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) is a major public health problem in sub-saharan Africa. Cytomegalovirus (CMV) has been reported to enhance HIV replication and accelerate the progression of HIV infection to AIDS. Objective: This study reports on the high seropositivity of immunoglobulin (Ig) G and M antibodies against CMV and the risk factors for CMV infection among HIV/AIDS patients in Ilorin, Nigeria. Method: A total of 180 consented HIV-1 seropositive patients (age-range 16-56 years; 108 females and 72 males) were consecutively recruited. Socio-demographic/behavioral data and 5 ml blood samples were collected from each patient. Plasma of each sample was assayed for anti-CMV IgG/IgM using a CMV IgG and IgM Enzyme Linked ImmunoSorbent Assay (ELISA) kit. Results: Twenty (11.1%) of the 180 HIV-1 seropositive subjects were positive for anti-CMV IgM antibody while 169(93.9%) were positive for anti-CMV IgG antibody. Age, marital status, number of sexual partners, CD4 cells counts and previous history of blood transfusion were the main correlates of CMV seropositivity among these patients. However, occupation, sex, highly active antiretroviral therapy (HAART) were not statistically associated with CMV seropositivity in this study. Conclusion: This study has shown that greater percentages of HIV-1 seropositive patients had active CMV infection. It has further shown that CMV is hyperendemic in HIV-1 seropositive patients in Ilorin, Nigeria.